Migrant visibility: Digitization and heritage policies - Faassen, Marijke van; Hoekstra, Rik (Frontiers in Human Dynamics, 2022)
Digitization and digital methods have had a big impact on migration history and history in general. The dispersed and fragmented nature of migration heritage that involves at least two countries and many cultural heritage institutions make it clear that migration history can be much improved by using digital means to connect collections. This makes it possible to overcome the biases that policy have introduced in private and public collections alike by selection and perspective. Digital methods are not immune to these biases and may even introduce new distortions because they often change heritage contextualizations. In this article, Van Faassen and Hoekstra argue that therefore they should be embedded in source criticism methodology. They use the example of post-World War II Dutch-Australian emigration to show how a migrant registration system can be used as a structural device to connect migrant heritage. They use methods from computer vision to assess the information distribution of the registration system. Together, connecting collections and information assessments give an encompassing view of the migrant visibility and invisibility in the heritage collections and perspectives for scholars to become aware of heritage biases.